Competitive Psychological Disposition and Perception of Performance in Young Female Soccer Players - Olmedilla, Aurelio; Ruiz-Barquín, Roberto; Ponseti, Francisco Javier; Robles-Palazón, Francisco Javier; García-Mas, Alexandre (Frontiers in Psychology, 2019)
The athlete’s psychological disposition is a factor that is increasingly considered by researchers as a key to sports performance, even as a mediator between the physical, technical and tactical abilities of the athlete and their competitive performance, thus acquiring great relevance in training and in sports performance. The purpose of this study is to analyze the psychological characteristics of young soccer players and their relation to their performance perception, made both by the player herself and by their coaches. The sample is composed of 108 women (Mage = 15.53, SDage = 1.05), with ages between 13 and 17 years (13 years, n = 1, 14 years, n = 18, 15 years, n = 36, 16 years, n = 29, 17 years, n = 24), and with a sport practice experience of 7.27 years on average (SD = 2.64). For to address this aim, we used the Psychological Characteristics related to the Sport Performance Questionnaire (CPRD) and the Psychological Skills Inventory for Sports (PSIS). In addition, regarding the evaluation of performance perception, an ad hoc short questionnaire was created, composed by one question addressed to the player and one directed to the coach. The results indicate that the group of players of the under-16 category obtained higher scores in all the psychological dimensions than the U-18 players, showing significant differences in Team Cohesion (p < .048). Regarding the degree of congruence between the player’s psychological features, and the player’s and coach’s performance perceptions, the results show statistically significant and negative correlations between the Team Cohesion factor and the athlete's own outcome perception for the match #1 (rxy = -. 479; p < .001), and match #2 (rxy = -. 402; p < .01). The results of this study may contribute to establish the differences between different constellations of psychological characteristics according to the categories of competition and their relationship with the perception of performance. This knowledge can be used by sports professionals: coaches, psychologists, physical educators, etc., in order to help athletes to reach their maximum performance.